Pelaksanaan Program Perencanaan Persalinan Dan Pencegahan Komplikasi (P4K) Melalui Peran Keluarga - Yusriani Yusriani; Muh. Said Mukharrim; Reza Aril Ahri (STIKIM Press, 2019)
The maternal mortality rate (MMR) is one of the important indicators of public health. AKI describes the number of women who die from a cause of death related to pregnancy disorders or treatment (excluding accident or incidental cases) during pregnancy, childbirth and during the puerperium (42 days after delivery) regardless of the length of pregnancy per 100,000 live births. South Sulawesi Province is one of the regions experiencing high maternal mortality problems, especially in Gowa Regency, namely in 2018 as many as 17 cases of maternal deaths, the highest cases of which were in the work area of Somba Opu Health Center, namely 5 cases. The general objective of this study is to analyze the role of the family in implementing the P4K program. The design of this study was qualitative with descriptive explanative design using purposive sampling technique with 33 informants consisting of 6 pregnant women, 4 husbands, 5 posyandu cadres, 3 village midwives, 1 coordinator midwife puskesmas, 8 heads environment and 6 village heads. The role of the family in implementing the P4K program in the work area of Somba Opu Health Center in Gowa Regency has been carried out but not optimally, there are still some indicators that have not been fulfilled.